Depression and all‐cause mortality risk in HIV‐infected and HIV‐uninfected US veterans: a cohort study1. Issue 5 (29th March 2019) - So‐Armah, K; Gupta, SK; Kundu, S; Stewart, JC; Goulet, JL; Butt, AA; Sico, JJ; Marconi, VC; Crystal, S; Rodriguez‐Barradas, MC; Budoff, M; Gibert, CL; et al.
Abstract : Objectives: The contribution of depression to mortality in adults with and without HIV infection is unclear. We hypothesized that depression increases mortality risk and that this association is stronger among those with HIV infection. Methods: Veterans Aging Cohort Study (VACS) data were analysed from the first clinic visit on or after 1 April 2003 (baseline) to 30 September 2015. Depression definitions were: (1) major depressive disorder defined using International Classification of Diseases, Ninth Revision (ICD‐9) codes; (2) depressive symptoms defined as Patient Health Questionnaire (PHQ)‐9 scores ≥ 10. The outcome was all‐cause mortality. Covariates were demographics, comorbid conditions and health behaviours. Results: Among 129 140 eligible participants, 30% had HIV infection, 16% had a major depressive disorder diagnosis, and 24% died over a median follow‐up time of 11 years. The death rate was 25.3 [95% confidence interval (CI) 25.0–25.6] deaths per 1000 person‐years. Major depressive disorder was associated with mortality [hazard ratio (HR) 1.04; 95% CI 1.01, 1.07]. This association was modified by HIV status (interaction P ‐value = 0.02). In HIV‐stratified analyses, depression was significantly associated with mortality among HIV‐uninfected veterans but not among those with HIV infection. Among those with PHQ‐9 data ( n  = 7372), 50% had HIV infection, 22% had PHQ‐9 scores ≥ 10, and 28% died over a median follow‐up time of 12 years. The death rate was 27.3 (95% CI 26.1–28.5) per 1000 person‐years. Depressive symptoms were associated with mortality (HR 1.16; 95% CI 1.04, 1.28). This association was modified by HIV status (interaction P ‐value = 0.05). In HIV‐stratified analyses, depressive symptoms were significantly associated with mortality among veterans with HIV infection but not among those without HIV infection. Conclusions: Depression was associated with all‐cause mortality. This association was modified by HIV status and method of depression ascertainment.